2011
DOI: 10.1590/s1516-14392011005000052
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ZnO2 nanoparticles on properties of concrete using ground granulated blast furnace Slag as binder

Abstract: In the present study, flexural strength together with pore structure, thermal behavior and microstructure of concrete containing ground granulated blast furnace slag with different amount of ZnO 2 nanoparticles has been investigated. Portland cement was replaced by different amounts of ground granulated blast furnace slag and the properties of concrete specimens were investigated. Although it negatively impact the properties of concrete, ground granulated blast furnace slag was found to improve the physical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The investigation into the microstructure by Feng et al [24] demonstrated that the incorporation of TiO 2 decreases the quantity of inner micro cracks in Portland cement paste. Nazari et al [30] investigated the effect of nano-TiO 2 on physical, thermal and mechanical properties of concrete using ground granulated blast furnace slag replacing OPC, showing that TiO 2 accelerates the formation of C-S-H gel and improves the pore structure.…”
mentioning
confidence: 99%
“…The investigation into the microstructure by Feng et al [24] demonstrated that the incorporation of TiO 2 decreases the quantity of inner micro cracks in Portland cement paste. Nazari et al [30] investigated the effect of nano-TiO 2 on physical, thermal and mechanical properties of concrete using ground granulated blast furnace slag replacing OPC, showing that TiO 2 accelerates the formation of C-S-H gel and improves the pore structure.…”
mentioning
confidence: 99%
“…In civil engineering field, most of the research works till date are conducted with nano-silica (nano-SiO 2 ) (NS) [7][8][9][10][11][12][13][14][15] and nano-titanium oxide (nano-TiO 2 ) (NT) [16][17][18][19][20][21]. On the other hand, a few studies were conducted with nano-Al 2 O 3 (NA) [7,[22][23][24][25][26], nanoFe 2 O 3 (NF) [27][28][29][30][31][32], nano-Fe 3 O 4 and nano-clay (NC) in comparison with those regarding NS or NT [33].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the literature reveals a great number of ways of effecting concrete nanomodification by different nanoparticles, such as nanosilica (nano-SiO 2 ), 1−11 nanotitanium oxide (nano-TiO 2 ), 6,12−15 nanoiron (nano-Fe 2 O 3 ), 5,11,16,17 nanoalumina (nano-Al 2 O 3 ), 18−21 zirconium dioxide (nano-ZrO 2 ), 22,23 nano copper oxide (nano-CuO), 24−26 zinc peroxide (nano-ZnO 2 ), 27 magnetic nanoparticles (iron carbide, Fe 3 C/C, and cobalt carbide, Co/C), 28 nanoclay particles, 29,30 carbon nanoparticles, 31−36 and so forth. Jo et al, 4 Qing et al, 8 and Li et al 16 determined that nano-SiO 2 can improve concrete workability and strength to increase resistance to water penetration, to accelerate the hydration reactions of both C 3 S and ash-cement mortar, and to help to control calcium leaching.…”
Section: ■ Introductionmentioning
confidence: 99%